Indoor Navigation System Based On Passive RFID Transponder With Digital Compass For Visually Impaired People - Mohamed Kassim, Anuar; Yasuno, Takashi; Suzuki, Hiroshi; Jaafar, Hazriq Izzuan; Mohd Aras, Mohd Shahrieel (The Science and Information Organization, 2016)
-